RNA N6‐Methyladenosine‐Binding Protein YTHDFs Redundantly Attenuate Cancer Immunity by Downregulating IFN‐γ Signaling in Gastric Cancer - Dongjun Jang; Chanwoong Hwa; Seoyeon Kim; Jaeik Oh; Seungjae Shin; Soo‐Jin Lee; Jiwon Kim; Sang Eun Lee; Yoojin Yang; Dohee Kim; Seoho Lee; Hae Rim Jung; et al. (Advanced Science)
Abstract Immunotherapy holds potential as a treatment for gastric cancer (GC), though immune checkpoint inhibitor (ICI) resistance remains an obstacle. One resistance mechanism involves defects in interferon‐γ (IFN‐γ) signaling, in which IFN‐γ is linked to improved responsiveness to ICIs. Herein, the roles of RNA N6‐methyladenosine (m6A) modifications in regulation of IFN‐γ signaling and the responsiveness to ICIs are unveiled. The m6A‐binding protein YTH N6‐methyladenosine RNA‐binding protein F1 (YTHDF1) is overexpressed in GC tissues, correlating with the suppression of cancer immunity and poorer survival rates. YTHDF1 overexpression impaired the responsiveness to IFN‐γ in GC cells, and knockdown studies indicated the redundant effects of YTHDF2 and YTHDF3 with YTHDF1 in IFN‐γ responsiveness. RNA immunoprecipitation sequencing revealed YTHDFs directly target interferon regulatory factor 1 (IRF1) mRNA, a master regulator of IFN‐γ signaling, leading to reduced RNA stability and consequent downregulation of IFN‐γ signaling. Furthermore, in mouse syngeneic tumor models, Ythdf1 depletion in cancer cells resulted in reduced tumor growth and increased tumor‐infiltrating lymphocytes, which are attributed to the augmentation of IFN‐γ signaling. Collectively, these findings highlight how YTHDFs modulate cancer immunity by influencing IFN‐γ signaling through IRF1 regulation, suggesting their viability as therapeutic targets in cancer immunotherapy.